THE ADAPTIVE STRATEGIES OF ISLAM KALANG COMMUNITY TOWARD SOCIAL CHANGES: A Case Study in Gemuh Kendal Central Java - Sulaiman, Sulaiman (Analisa: Journal of Social Science and Religion, 2018)
Islam Kalang is Muslim community that still preserves indigenous traditional Javanese values. This study aimed at figuring out adaptive strategies of the community in social changes. It used a qualitative method and employed observation, in-depth interview, and documentation as techniques for data collection.The findings were that Islam Kalang has something in common Javanese society in a way that they are inclusive and open towards their surroundings. This community can be grouped into two types; the active group represented by santri, and the other one is not active as performed by abangan. The two groups perform Kalang traditions, though they are active in doing religious prescriptions, five-time prayers, alms, fast, and pilgrimage. It is due to the fact that they have strong beliefs in doing their traditional rituals. For the community, their primary duty is to do rites inherited by their predecessors, i.e., when they perform obong mitungdino, and obong sependhak. They have undergone changes and shifts because of da’wah Islamiyah and marriage with other groups. It means, therefore, the community has adaptive strategies in order to survive in the midst of society. The strategies include strong trust, endogamic marriage, and accommodating attitude.By these strategies, the community can embed and practice Kalang traditional values.